ACTORS IN INDUSTRIAL RELATIONS: GROWTHS AND DWARFISM OF INDUSTRIAL RELATIONS SYSTEM IN NIGERIA (Malaysian Management Journal, 2020)
The study focused on the actors in industrial relations and their contributions towards the growth and dwarfism of Nigeria’s industrial relations system. It identified some problems which have been brought by other actors in industrial relations - the employees. In pursuit of the previously mentioned objectives, a survey research was employed. The population used for the study was 160 staff of Micheal Imoudu Institute for Labour Studies, Ilorin, Nigeria. A sample size of 114 was determined using Taro Yamani’s formula (1964). The study made use of both primary and secondary data and questionnaires were administered to 114 staff but only 99 were collected, analysed and interpreted. The multiple regression analysis was used to test the hypotheses at 0.05 significant level using SPSS v.20. It was found that governments at all levels have significant impacts on the growth and dwarfism of the industrial relations system of Nigeria. The study concluded that actors in industrial relations in Nigeria affect the growths and dwarfisms of Nigeria’s industrial relations system and it is recommended that further research be extended to other industries such as construction, agriculture and telecommunication. The study can also be used as guidelines for human resource aficionados and industrial relations experts.